2020
DOI: 10.4103/ijri.ijri_423_19
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of median neuropathy at the carpal tunnel: Thrombosis of the persistent median artery

Abstract: Carpal tunnel syndrome is a common peripheral nerve entrapment neuropathy caused due to compression of the median nerve at the level of the wrist joint. Bifid median nerve associated with a persistent median artery is a rare entity and in itself asymptomatic anatomical variant. However, distension of the persistent median artery due to a thrombus can be symptomatic due to compression on the median nerve and can compromise the blood flow to the palm. We report a case of persistent median artery thrombosis in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Additionally, this artery pierced the median nerve and was found to have the same anatomical composition bilaterally. Although persistent median arteries contributing to a portion of the hand's blood supply have been described, none appeared to have made as signi cant a contribution as was seen in this case [4,5]. Haladaj et al reported various contributions to the super cial palmar arch, however the extent of vascular supply was less than in this case.…”
Section: Discussionmentioning
confidence: 47%
“…Additionally, this artery pierced the median nerve and was found to have the same anatomical composition bilaterally. Although persistent median arteries contributing to a portion of the hand's blood supply have been described, none appeared to have made as signi cant a contribution as was seen in this case [4,5]. Haladaj et al reported various contributions to the super cial palmar arch, however the extent of vascular supply was less than in this case.…”
Section: Discussionmentioning
confidence: 47%
“…Rarely, PMAs have been found to coexist with a bifid median nerve (BMN) [6][7][8][9][10][11][12] . The presence of a persistent median artery (PMA) has been reported to be associated with the occurrence of compression neuropathy 2,3,5,[13][14][15] -caused directly or secondary to associated pathology of the PMA including calcification, atherosclerosis, and thrombosis [16][17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%